2017
DOI: 10.1007/s00894-017-3419-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding energy profiles of full agonists, partial agonists, and antagonists of the α7 nicotinic acetylcholine receptor

Abstract: Nicotinic acetylcholine receptors (nAChRs) belong to the Cys-loop receptor family and are important drug targets for the treatment of neurological diseases. However, the precise determinants of the binding efficacies of ligands for these receptors are unclear. Therefore, in this study, the binding energy profiles of various ligands (full agonists, partial agonists, and antagonists) were quantified by docking those ligands with structural ensembles of the α7 nAChR exhibiting different degrees of C-loop closure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A proposed paradigm of antagonism compared to agonism of nAChRs is that agonists stabilise the C‐loop into a relatively closed conformation whereas antagonist binding results in a larger opening of the C‐loop (Tabassum, Ma, Wu, Jiang, & Yu, ). In our simulations, the C‐loop of the α4β2 nAChR/DHβE displayed an open conformation similar to that of the crystal structure of the complex between AChBP and DHβE (Shahsavar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A proposed paradigm of antagonism compared to agonism of nAChRs is that agonists stabilise the C‐loop into a relatively closed conformation whereas antagonist binding results in a larger opening of the C‐loop (Tabassum, Ma, Wu, Jiang, & Yu, ). In our simulations, the C‐loop of the α4β2 nAChR/DHβE displayed an open conformation similar to that of the crystal structure of the complex between AChBP and DHβE (Shahsavar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies have confirmed that ligands with different efficacies on nAChRs also induce different conformations of AChBP. 26–28 In the Concentration Response Curves (CRC's) tubocurarine (antagonist) shows a smaller ΔSHG than the other compounds, confirming that the SHG assay was able to distinguish conformational changes induced by these compounds in an AChBP conjugate labelled on K158. The experiment also indicated that the probe's location in the orthosteric site did not block the binding of these well-studied ligands.…”
Section: Resultsmentioning
confidence: 71%